Prognostic factors for success in treating kidney stones by extracorporeal shock wave lithotripsy - Chongruksut W. (2014)
Background: Extracorporeal shock wave lithotripsy (ESWL) is widely used worldwide to treat kidney stone because it is without invasive and can be done on an outpatient basis. However, not all patients are treated successfully. The success of kidney stone treatment by ESWL depends on several factors. Objective: To investigate prognostic factors for the successful treatment of kidney stones by ESWL. Material and Method: A prospective cohort study was made of 394 patients with kidney stone who underwent ESWL using Storz SLX-20 Lithotripter at Chiang Mai University Hospital between June 2008 and October 2009. All patients were followed up for three months after treatment to evaluate treatment success. Success was defined as the presence of clinically insignificant residual fragments less than or equal to 4 mm or complete clearance of the stones. Data were analyzed using exponential risk regression to determine the prognostic factors of ESWL treatment success. Results: The ESWL treatment success rate was 81.2%. The stone free (SF) rate was 56.4%. The clinically insignificant residual fragment (CIRF) rate was 24.8%. The median number of ESWL treatment sessions was two (IQR = 2-4). Multivariable exponential risk regression analysis demonstrated that the statistically significant prognostic factors for ESWL treatment were stone size < 15 mm (IRR = 1.52, 95% CI = 1.13-2.05, p = 0.005), stone location (renal pelvis had a higher success rate than lower calyx; IRR = 1.32, 95% CI = 1.01-1.72, p = 0.028) and a single stone (IRR = 1.35, 95% CI = 1.02-1.79, p = 0.035). Conclusion: Stone size, stone location, and stone number were prognostic factors in determining the success of ESWL treatment.